New crosslinked hydrazide–based polymers as Cr(VI) ions adsorbents. Issue 6 (December 2017) - Dautoo, Umesh K.; Shandil, Yashwant; Chauhan, Ghanshyam S.
Graphical abstract: Two new crosslinked polymers were synthesized by simple and green protocol and evaluated as Cr(VI) ions adsorbents with high efficiency even at very low concentration of 1.0 ppm with rapid adsorption are reported herein. Highlights: New hydrazide-based nanopolymers, differing only in the nature of crosslinker, were synthesized. These nanopolymers were evaluated as Cr(VI) adsorbents. These exhibited high rapid removal with high adsorption capacity of the targeted ions. Adsorption capacity is very high even at 1.0 ppm. Abstract: Cr(VI) salts are abundantly used in the industrial processes, but they have become serious water pollutants and their removal from the wastewaters is a huge challenge. In the present study, two new crosslinked polymers having hydrazide functional group, differing in the nature of crosslinking agents ethyleneglycol dimethacrylate or divinyl benzene, were synthesized for use as Cr(VI) ion adsorbents. These were analysed by FTIR, SEM, EDS, TEM, AFM and XRD to confirm their structure. The adsorption parameters such as contact time, temperature, pH and Cr(VI) ions concentration were investigated. Adsorption of Cr(VI) ions was rapid, pH dependent, and up to 100% adsorption from 100 ppm solution was observed within 1 min at pH = 2.0 and 25 °C. Langmuir isotherm best fitted the experimental values. These adsorbents, synthesized by a simple green protocol, show 100% adsorption efficiency even at a very low concentration of 1.0 ppm. Adsorption kinetics, mechanism and thermodynamics of the adsorption process were also investigated.